Superantigenic properties of the group A streptococcal exotoxin SpeF (MF). - Norrby-Teglund, A (1994)
Streptococcal pyrogenic exotoxin F (SpeF), previously referred to as mitogenic factor, is a newly described potent mitogen produced by group A streptococci. To investigate whether this protein belongs to the family of microbial superantigens, we analyzed the cellular and molecular requirements for its presentation to T cells and compared it with the known streptococcal superantigen pyrogenic exotoxin A (SpeA) and the nonspecific polyclonal T-cell mitogen phytohemagglutinin (PHA). SpeF and SpeA were efficiently presented by autologous antigen-presenting cells (APCs) and an allogeneic B lymphoma cell line, Raji. In contrast, the monocytic cell line U937, which does not express major histocompatibility complex (MHC) class II molecules, failed to present SpeF as well as SpeA but supported the response to PHA. Thus, the presentation of SpeF by APCs was class II dependent but not MHC restricted. The requirement for HLA class II was further supported by the ability of anti-HLA-DQ monoclonal antibody to block the SpeF-induced proliferative response by 75 to 100%. Paraformaldehyde (PFA) fixation of autologous APCs resulted in an impaired ability of SpeF and SpeA to induce optimal T-cell proliferation. In contrast, fixation of Raji cells did not affect the induced proliferation. The stimulatory effect of PHA remained unaffected by both the use of PFA-fixed APCs and the addition of the HLA class II-specific monoclonal antibodies. The addition of a supernatant enriched in interleukin 1 and interleukin 6 to fixed autologous APCs resulted in an increased SpeF-induced response; thus, the impairment was not due to a requirement for processing, but, rather, costimulatory factors produced by metabolically active APCs were needed. SpeF was found to preferentially activate T cells bearing V beta 2, 4, 8, 15, and 19, as determined by quantitative PCR. The data presented clearly show that SpeF is a superantigen. We also studied the prevalence of the speF gene in clinical isolates by Southern blot analyses, and the gene could be detected in 42 group A streptococcal strains, which represented 14 serotypes.